Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Q: solve the ff.equation for the variable present. 2x-3(x-2)=5+2
A: 2x-3(x-2)=5+2 2x - 3x + 6 = 7 -x + 6 = 7 -x = 7 - 6 -x = 1 x = -1
Original conversation
User: solve the ff.equation for the variable present. 2x-3(x-2)=5+2

Weegy:

Question
Asked 9/13/2009 6:44:40 PM
Updated 2/17/2014 4:10:07 PM
This conversation has been flagged as incorrect.
Flagged by andrewpallarca [2/17/2014 4:10:07 PM]
Rating
3
2x-3(x-2)=5+2

2x - 3x + 6 = 7

-x + 6 = 7

-x = 7 - 6

-x = 1

x = -1
Added 2/17/2014 4:10:04 PM
This answer has been confirmed as correct and helpful.
2x-3(x-2)=5+2
2x + -3(x + -2) = 5 + 2
2x + -3(-2 + x) = 5 + 2
2x + 6 + -3x = 5 + 2
6 + 2x + -3x = 5 + 2
6 + -1x = 7
-1x = 7 + -6
-1x = 1
Divide each side by '-1'.
x = -1

Added 9/14/2009 4:53:21 AM
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 247 [Total 265] Ratings 0 Comments 177 Invitations 7 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 115 [Total 266] Ratings 1 Comments 5 Invitations 10 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.